Revisiting the concept of knowledge in classical Islamic philosophy: Toward an integrated conceptual framework - Syafa’atus Syarifah; Khaerudin (Mishkat: Journal of Theology and Civilization, 2026)
The concept of knowledge in classical Islamic philosophy has been widely studied; however, most existing studies focus on individual philosophers, leaving the conceptual relationships among their ideas unexplained as a coherent conceptual system. This study aims to analyze and integrate the concept of knowledge in classical Islamic philosophy through a conceptual synthesis of the thought of Al-Kindī, Al-Fārābī, Ibn Sīnā, Al-Ghazālī, Ibn Rushd, and Ibn Khaldūn. The study employed a qualitative library research approach using conceptual analysis and philosophical synthesis. The findings reveal that the concept of knowledge is structured around four interconnected dimensions: ontological foundation, structure of knowledge, epistemological integration, and civilizational orientation. These findings demonstrate that the differences among classical Muslim philosophers represent functional differentiation rather than conceptual fragmentation within a coherent framework of knowledge. This study contributes by proposing an integrated conceptual framework that provides a theoretical foundation for advancing contemporary studies in Islamic philosophy of knowledge. Abstrak Konsep ilmu dalam tradisi filsafat Islam klasik telah banyak dikaji, namun sebagian besar penelitian masih berfokus pada pemikiran individual para filsuf sehingga hubungan konseptual antargagasan belum dirumuskan sebagai suatu sistem konseptual yang utuh. Penelitian ini bertujuan menganalisis dan mengintegrasikan konsep ilmu dalam tradisi filsafat Islam klasik melalui sintesis konseptual terhadap pemikiran Al-Kindī, Al-Fārābī, Ibn Sīnā, Al-Ghazālī, Ibn Rushd, dan Ibn Khaldūn. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian kepustakaan melalui analisis konseptual dan sintesis filosofis. Hasil penelitian menunjukkan bahwa konsep ilmu tersusun atas empat dimensi yang saling berkaitan, yaitu fondasi ontologis, struktur keilmuan, integrasi epistemologis, dan orientasi peradaban. Temuan ini menunjukkan bahwa perbedaan pemikiran para filsuf bukan merupakan fragmentasi konsep ilmu, melainkan diferensiasi fungsi dalam satu kerangka konseptual yang koheren. Penelitian ini berkontribusi dengan menawarkan kerangka konseptual terintegrasi sebagai landasan teoritis bagi pengembangan filsafat ilmu Islam kontemporer.